Dietary Modifications in IBS Leads to Reduced Symptoms, Weight, and Lipid Levels : Two Randomized Clinical Trials - Roth, Bodil; Ohlsson, Bodil (Nutrients, 2025)
Background/Objectives: Irritable bowel syndrome (IBS) is presented with both gastrointestinal and extraintestinal symptoms. In addition, overweight/obesity and metabolic syndrome is prevalent in IBS. Dietary interventions with a low content of fermentable oligo-, di-, and monosaccharides and polyols (FODMAP) or a starch- and sucrose-reduced diet (SSRD) efficiently reduce symptoms and weight. Our hypothesis was that not only nutrition composition but also weight reduction is of importance for symptom relief. The aim was to merge two randomized trials and examine symptoms, weight, nutrition intake, and lipid levels at baseline and during nutritional intervention. Methods: One study with 105 IBS patients randomized to either an SSRD (n = 80) or control diet (n = 25) and one study with 155 IBS patients randomized to an SSRD (n = 77) or low FODMAP (n = 78) were merged. Symptom and food questionnaires were analyzed together with weight/body mass index (BMI) and lipid levels. Results: Patients had moderate or severe IBS at baseline, and half of them were overweight/obese. Energy intake was reduced by both diets, with the most pronounced carbohydrate reduction after the SSRD. The cholesterol levels were highest in the second cohort, possibly due to the higher fat and lower starch intake. About 25% had high-density lipoprotein below reference levels. Gastrointestinal and extraintestinal symptoms, as well as weight/BMI, were reduced by the SSRD and low FODMAP, but not in the control group. The SSRD in the second cohort and low FODMAP rendered lower levels of total cholesterol, low-density lipoprotein, and non-high-density lipoprotein levels. Weight/BMI were more often associated with lipid levels and symptoms than nutrient composition at baseline, and weight/BMI reductions correlated with carbohydrate reduction and were associated with a reduction in gastrointestinal and extraintestinal symptoms. Conclusions: Not only food components, but also overweight/obesity may be of importance for the development and severity of IBS and related symptoms.
Keywords: dietary habits; irritable bowel syndrome; lipid profile; low FODMAP; SSRD; symptoms; weight